Professional specialization as a factor of overseas emigration in the 16th and 17th centuries - Andrade Cardoso, Diogo (2018)
This paper demonstrates the connection between the emigrants’ professional specialization and their choice of an overseas destination and the best time to emigrate during the period from 1560 to 1651. Using Vila do Conde parish and notary records, this research extracts information on the emigrants’ professions and compares it with the local economic and social trends, demonstrating that this was an important emigration factor to those looking for a better life, since their profession allowed them a better adjustment to the economic and social realities at the destination.